2022
DOI: 10.3390/s22228648
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Sensitive Molecularly Imprinted Polymer (MIP)-Coated Microwave Glucose Sensor

Amir Hossein Omidvar,
Atena Amanati Shahri,
Ariana Lacorte Caniato Serrano
et al.

Abstract: A novel, low-cost, sensitive microwave microfluidic glucose detecting biosensor incorporating molecularly imprinted polymer (MIP) is presented. The sensing device is based on a stub resonator to characterize water glucose solutions. The tip of one of the stubs is coated with MIP to increase the selectivity of the sensor and hence the sensitivity compared to the uncoated or to the coated with non-imprinted polymer (NIP) sensor. The sensor was fabricated on a FR4 substrate for low-cost purposes. In the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…This limitation may impact their ability to measure rapid changes, as their binding to the substrate is based on the equilibrium between levodopa concentration and the number of available binding sites. Several groups have developed continuous sensors for small molecules such as vancomycin and glucose using both aptamers and molecularly imprinted polymers. Despite these few successful examples, a continuous sensor employing a nonenzymatic, affinity-based biosensing molecule has yet to be achieved. To the best of the authors’ knowledge, there have been no reported instances of levodopa sensing using aptamers or antibodies.…”
Section: Detection Strategies Of Levodopamentioning
confidence: 99%
“…This limitation may impact their ability to measure rapid changes, as their binding to the substrate is based on the equilibrium between levodopa concentration and the number of available binding sites. Several groups have developed continuous sensors for small molecules such as vancomycin and glucose using both aptamers and molecularly imprinted polymers. Despite these few successful examples, a continuous sensor employing a nonenzymatic, affinity-based biosensing molecule has yet to be achieved. To the best of the authors’ knowledge, there have been no reported instances of levodopa sensing using aptamers or antibodies.…”
Section: Detection Strategies Of Levodopamentioning
confidence: 99%
“…The sensor was selective to glucose, since no shift in frequency was observed when NIP, and solutions of mannose and galactose were used. The sensor response was linear in the range of 0.5 mg/mL–to 4 mg/mL of glucose with a lower limit of detection (LLD) of 24 pg/mL [ 93 ]. In another study, Sehit et al fabricated an MIP sensor for the detection of glucose by electropolymerization of o-PD (monomer), glucose (template), and gold nanoparticles (AuNPs) on a bare gold electrode.…”
Section: Detection Of Skeletal and Cardiac Muscle Analytes With Mipsmentioning
confidence: 99%